Bipedal hopping timed to a metronome to detect impairments in anticipatory motor control in people with mild multiple sclerosis. (June 2018) - Kirkland, Megan C.; Chen, Alice; Downer, Matthew B.; Holloway, Brett J.; Wallack, Elizabeth M.; Lockyer, Evan J.; Buckle, Natasha C.M.; Abbott, Courtney L.; Ploughman, Michelle
Abstract: Background: People with mild multiple sclerosis (MS) often report subtle deficits in balance and cognition but display no measurable impairment on clinical assessments. We examined whether hopping to a metronome beat had the potential to detect anticipatory motor control deficits among people with mild MS (Expanded Disability Status Scale ≤ 3.5). Methods: Participants with MS ( n  = 13), matched controls ( n  = 9), and elderly subjects (n = 13) completed tests of cognition (Montreal Cognitive Assessment (MoCA)) and motor performance (Timed 25 Foot Walk Test (T25FWT)). Participants performed two bipedal hopping tasks: at 40 beats/min (bpm) and 60-bpm in random order. Hop characteristics (length, symmetry, variability) and delay from the metronome beat were extracted from an instrumented walkway and compared between groups. Results: The MS group became more delayed from the metronome beat over time whereas elderly subjects tended to hop closer to the beat (F = 4.52, p  = 0.02). Delay of the first hop during 60-bpm predicted cognition in people with MS ( R  = 0.55, β = 4.64 (SD 4.63), F = 4.85, p  = 0.05) but not among control ( R  = 0.07, p  = 0.86) or elderly subjects ( R  = 0.17, p  = 0.57). In terms of hopping characteristics, at 60-bpm, people with MS and matched controls were significantly different from the elderly group. However, at 40-bpm, the MS group was no longer significantly different from the elderly group, even though matched controls and elderly still differed significantly. Conclusions: This new timed hopping test may be able to detect both physical ability, and feed-forward anticipatory control impairments in people with mild MS. Hopping at a frequency of 40-bpm seemed more challenging. Several aspects of anticipatory motor control can be measured: including reaction time to the first metronome cue and the ability to adapt and anticipate the beat over time. Highlights: Hopping at metronome frequency of 40 bpm was more challenging than 60 bpm. MS patients did not adapt to the metronome beat to the same extent as controls. Metronome timing predicted cognition in people with MS but not controls. Hop length and consistency predicted performance on the Timed 25-ft Walk Test. Metronome hopping detects both physical ability and anticipatory control impairments.